TRIGONOMETRY IN A GALILEAN PLANE - Ismoilov Sherzodbek; Kholmurodova Gulnoza (Bright Mind Publishing, 2025)
The parabolic trigonometry in the Galilean plane is introduced in analogy to thesimple and hyperbolic trigonometries in the Euclidean and Minkowski planes. Inthis paper we will introduce parabolic functions and their properties in the Galileanplane.